EFFECT OF HORMONAL AND HERBAL THERAPIES ON POSTPARTUM PLASMA PROFILE OF GLUCOSE AND TOTAL PROTEIN IN HOLSTEIN FRIESIAN COWS - PATEL, B B; PATEL, D M; PATEL, J A (The Indian Journal of Animal Reproduction, 2023)
Twenty-eight freshly calved HF cows of University farm were monitored through clinical diagnosis and fortnightly plasma profile of glucose and total protein from the day of calving till 75 days postpartum. Blood glucose and protein status was also studied at 6 and 24 h postpartum in all the animals. The animals were randomly and equally divided into four groups, each of seven animals. Group I served as Control; Group II included PGF2 ,: 500 μg (lliren) i/m alone and Group Ill PGF2r: 500 μg (lliren) plus Oxytocin 50 units i/m immediately after parturition, while Group IV was treated with intra-uterine infusion of herbal ecbolic (Vantab) at weekly interval thrice. The regression of pregnancy CL, uterine involution, first and fertile estrus postpartum were significantly earlier/shorter in PG treated than the herbal treated and control group. The overall mean plasma glucose and total protein concentrations were 57.79 0 0.50 (range 50 to 67) mg/di and 7.25 0 0.05 (range 6.65 to 7.87) g/dl, respectively. The differences between groups were highly significant (P<0.01) for plasma glucose profile only, while differences between periods were highly significant (P<0.01) for both glucose and protein. The values of glucose declined significantly within 24 hrs of calving, which further declined to the lowest level around day 15-30 postpartum and then again rose steadily till 60-75 days postpartum. Plasma protein levels were also significantly low around day 15-30 postpartum as compared to other periods of study. These changes were associated with stress of calving, lactation and uterine involution.